Effectiveness of a Digital Self-Regulated Learning Model in Hypertension Education - Prima Trisna Aji; Tukimin bin Sansuwito; Chua Siew Kuan (Universitas Negeri Makassar, 2026)
Conventional hypertension education often emphasizes information delivery without systematically fostering learner autonomy and sustained behavioral regulation. This study developed and tested a Digital Self-Regulated Learning (SRL) model designed to transform chronic disease education into a structured, technology-enhanced learning process. A quasi-experimental pretest-posttest control group design was conducted involving adults diagnosed with hypertension. The experimental group received an eight-week SRL-based digital intervention integrating goal setting, strategic planning, self-monitoring, and reflective evaluation, while the control group received conventional education. Validated instruments measured self-regulation competence, hypertension knowledge, and self-management behavior. Independent and paired-sample analyses demonstrated significant improvements in the experimental group across all primary outcomes compared to the control group. Structural Equation Modeling further indicated that hypertension knowledge partially mediated the relationship between self-regulation competence and behavioral adherence. These findings provide empirical evidence that theory-driven digital instructional design enhances learner agency and supports sustainable self-management. The study contributes to educational innovation research by positioning chronic disease education within a structured pedagogical framework rather than a purely informational model.